Teaching Practice Research of Narrative Pedagogy with the Forensic Innocence - Chun-Mei Tsai; Cheng-Pin Lai (National Taipei University of Education, 2022)
Piloted in September 2020, this semester-long study was conducted in order to help university students better understand social issues, such as wrongful convictions or miscarriages, and help them be able to analyze issues from different perspectives. Using a narrative pedagogy approach, 40 psychology students were asked to read original court judgments, analyze news reports, and speak with those wrongfully convicted. The researchers then analyzed how students perceived those wrongfully convicted, understood the judicial system, and developed communication skills. Ultimately, students showed improved critical thinking, evaluation of sources, and communication skills. As a result of the narrative pedagogical approach, some students were able to put themselves in the position of those wrongfully convicted and, in some cases, even connect to their own personal experiences. The narrative approach allowed interaction between each of the three parties (the class), the guests (those wrongfully convinced), and the audience (the teacher and students). This study evaluates the course, reviews student feedback, and provides future recommendations.